Critical stresses induced by wheel load and braking forces in flexible pavements - Srisawat Ahviphun; Prof. Utai Voodhigula; Dr. Chai Muktabhant; Prof. John Hugh Jones; Dean Milton E. Bender Jr. (Bangkok : SEATO Graduate School of Engineering, 1964)
In most flexible pavement analysis only vertical load is considered; this thesis is concerned primarily with effects resulting from the addition of a horizontal load applied at pavement surface. A horizontal load is created by deceleration of a vehicle on the pavement. In this study the braking force was assumed to be 30 percent of the wheel load. The equations used in this paper are those derived by Vicharn Danvivathana, for the case of homogeneous, isotropic, elastic materials of infinite extent when Poisson's ratio is equal to 0.5. A 9000-lb wheel load was selected for the analytical example. Tires were in the 11.00 series, with a tread width of 8.00 in. and inflation pressure of 90 psi. The analysis indicates that the shear force caused by braking of a vehicle induces significant stresses in the pavement system. This effect is especially pronounced at shallow depths under the pavement surface and should not be ignored in pavement design.
Thesis (M.Eng.) - SEATO Graduate School of Engineering
A thesis submitted in partial fulfillment if the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Keywords: Pavements -- Testing; Strains and stresses